Small Bowel Phytobezoar Obstruction in a Post Gastrojejunostomy Patient A Case Report - Ullah, SM Jafar; Kawsar, KA (Journal of Bangladesh College of Physicians and Surgeons, 2010)
Small bowel phytobezoars are, though well-known, a rare cause of mechanical intestinal obstruction. It occurs mainly in the patients who had a previous gastric operation.We present a case of phytobezoar obstruction in a patient, who underwent gastrojejunostomy operation. We also report here a rare radiological finding of phytobezoar obstruction. The patient was treated surgically and had an uneventful recovery. DOI: 10.3329/jbcps.v27i2.4253 J Bangladesh Coll Phys Surg 2009; 27: 99-102